Family Health Literacy, Family Functioning, and Type 2 Diabetes Self-Management in the Context of Informal Caregiving: An Embedded Mixed-Methods Multiple-Case Study - Filipa Pinheiro; Maria Odete Amaral; Ana Filipa Loureiro (Healthcare, 2026)
Background/Objectives: Type 2 diabetes is a prevalent chronic disease that requires continuous self-management and adaptation by both individuals and their families. Health literacy is recognised as an important determinant of chronic disease management, influencing the ability to access, understand, and use health information. This study aimed to explore how family health literacy and family functioning were related to type 2 diabetes self-management across four family cases in the context of informal caregiving and to describe the changes observed following tailored family nursing interventions. Methods: An embedded mixed-methods multiple-case study was conducted with four families receiving care in a Portuguese primary healthcare unit. Qualitative data were obtained through structured family interviews guided by the Dynamic Model of Family Assessment and Intervention. Quantitative data were collected using family assessment instruments and the Diabetes Self-Care Activities Scale. Each family was analysed as an individual case, followed by cross-case comparison and integration of qualitative and quantitative findings. Results: Across the four cases, the ability to understand and translate diabetes-related information into family routines varied and was associated with differences in self-management practices. Within-case comparisons identified case-specific changes in family communication, mutual support, selected family nursing diagnoses, and some diabetes self-care behaviours. Medication adherence and blood glucose monitoring were more consistently maintained than dietary management, physical activity, and foot care. Conclusions: Family health literacy appeared to operate as a relational and context-dependent resource associated with how diabetes-related recommendations were negotiated and incorporated into daily family routines. Tailored family nursing interventions were followed by case-specific changes; however, the study design does not allow causal attribution.